2005
DOI: 10.1002/eet.372
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for afforestation externalities: a comparison of contingent valuation and choice modelling

Abstract: One issue faced by those using social cost-benefit analysis to make decisions on forestation is how to account for environmental externalities. This paper compares two different valuation techniques, contingent valuation and choice modelling. Both approaches were applied to an afforestation programme in the northeast of Spain, and were found to yield similar estimates of welfare change when the utility function was fully specified. However, when elements of the utility function were omitted, significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
1
15
0
2
Order By: Relevance
“…This practice, combined with the drop in wood prices in the past few decades, the shortage of manual labour, the decreased market for small diameter timber and the high costs of wood transportation has resulted in a serious decrease in the economic viability of the forestry sector (Mogas et al, 2005). A direct consequence of this loss has been the gradual decrease in the rural population (Aubarell et al, 1999), especially in mountainous areas.…”
Section: Introductionmentioning
confidence: 98%
“…This practice, combined with the drop in wood prices in the past few decades, the shortage of manual labour, the decreased market for small diameter timber and the high costs of wood transportation has resulted in a serious decrease in the economic viability of the forestry sector (Mogas et al, 2005). A direct consequence of this loss has been the gradual decrease in the rural population (Aubarell et al, 1999), especially in mountainous areas.…”
Section: Introductionmentioning
confidence: 98%
“…A recent survey demonstrated that Catalonians are willing to pay for the experience of picking wild mushrooms [17]. Consequently we could expect incentives for improved forest management.…”
Section: Introductionmentioning
confidence: 99%
“…Only some general statements have been made claiming that CE generates a lower number of protest responses. For example, Mogas et al (2005) argue that the lower response rate they observed in their CV compared to their CE was due to a 'protest motive' in CV. However, they do not detail this protest motive any further.…”
Section: Introductionmentioning
confidence: 92%